The existence of (sodium, potassium and calcium) ionophores in different membranes and their possible clinical importance - Ciliv, Gönenç (The Turkish Journal of Pediatrics, 1976)
As an approach to elucidate the complicated structure of cell membranes, we looked for the existence of molecules with ionophore characteristics in different natural membrane fractions. It was found that a fraction of the white matter of bovine brain, the electric organ of the eel and a membrane of Halobacterium halobium act as an ionophore for sodium; in addition to this, a fraction of the gray matter of bovine brain and muscle endoplasmic reticulum act as an ionophore for potassium. There was also evidence that bovine heart mitochondria membrane fractions are very effective in the transport of potassium and calcium. Now it is necessary to identify these structures, like the proteins responsible for the transport of anions in the human erythrocyte membranes, and to look for their role in different clinical situations.